2017
DOI: 10.1002/lary.26759
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway surgery for obstructive sleep apnea reduces blood pressure

Abstract: 4. Laryngoscope, 128:523-527, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Systematic reviews have only shown a decrease of 2.6 to 2.7 mmHg in SBP and 2.0 to 2.7 mmHg in DBP [61][62][63] . Other studies [142][143][144] have shown that sleep surgery may have a positive effect on blood pressure and other cardiovascular endpoints, but the evaluation of these relationships is difficult because there is no standard surgical procedure to treat OSA in adults. The overall evidence for improvement in cardiovascular endpoints after surgical treatment is weak, and, thus, there is a need for RCTs 66 .…”
Section: Paper I -Does Surgical Treatment For Obstructive Sleep Apneamentioning
confidence: 99%
“…Systematic reviews have only shown a decrease of 2.6 to 2.7 mmHg in SBP and 2.0 to 2.7 mmHg in DBP [61][62][63] . Other studies [142][143][144] have shown that sleep surgery may have a positive effect on blood pressure and other cardiovascular endpoints, but the evaluation of these relationships is difficult because there is no standard surgical procedure to treat OSA in adults. The overall evidence for improvement in cardiovascular endpoints after surgical treatment is weak, and, thus, there is a need for RCTs 66 .…”
Section: Paper I -Does Surgical Treatment For Obstructive Sleep Apneamentioning
confidence: 99%
“…de Paula Soares et al 22 showed in a small 18-patient group with OSA that following upper airway surgery, the mean systolic pressure reduced by 7.4 mm Hg, whereas the mean diastolic pressure reduced by 4.2 mm Hg at a 6-month follow-up. Pang et al 23 studied 112 patients with OSA and revealed the mean preoperative and postoperative SBP reduced from 146 ± 15.3 mm Hg to 122 ± 12.5 mm Hg ( P < .001), and DBP reduced from 91 ± 10.2 mm Hg to 76 ± 7.8 mm Hg ( P < .001). However, Pang’s study only examined blood pressure at 1 time point in a day before and after upper airway surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of rescue surgery to reduce DBP was also evaluated using a meta-analysis of 9 observational studies. 86,124,144,151,152,190,206,212,262 The meta-analysis demonstrated a clinically significant reduction in DBP of -2.7 mm Hg (95% CI: -7.9 to 2.5 mm Hg) with rescue therapy in adults with OSA (see supplemental material, Figure S18). The quality of evidence was low due to risk of bias associated with observational studies.…”
Section: Blood Pressurementioning
confidence: 97%
“…The efficacy of rescue surgery to reduce BP was evaluated using a an analysis of 1 RCT 38 and a meta-analysis of 10 observational studies. 86,124,144,151,152,190,206,212,219,262 The RCT 38 included mostly middle-aged participants with moderate to severe OSA who had failed conventional A c c e p t e d P a p e r treatment, and were allocated to multilevel upper airway surgery or medical management and followed for 6 months. The observational studies included retrospective, and prospective cohort and case-control designs.…”
Section: Blood Pressurementioning
confidence: 99%